'Place‐ing' fear of crime. (14th July 2015) - Innes, Martin
<x xml:space="preserve">Abstract</x> This commentary seeks to situate the work of Solymosi, Bowers, and Fujiyama (2015) in the literature on fear of crime, identifying several future opportunities where the methodological innovations they describe could be gainfully applied.